SISTEM INFORMASI GEOGRAFIS PEMETAAN FASILITAS KOTA TEMBILAHAN - Suhefi Oktarian; Usman Usman (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2016)
Indragiri Hilir district is the largest district in the province of Riau and centered on the District Tembilahan. As the central regions of kabupaten Inhil the development of facilities in the city of Tembilahan certainly progressed so rapidly. Based on data from the official website of the district government in 2016 Inhil www.goinhil.com only provide information Tembilahan municipal facilities in the form of a table, another problem is not managed on a centralized processing facility data Tembilahan city which caused no information showing the location of facilities that can be dynamically shaped in this case GIS in city Tembilahan. By using geographic information systems, public facilities can dipublis information dynamically and become as an information to the public both within and newcomers remember Tembilahan city is the center of Kabuapten indragiri downstream. This system was developed using MS4W and applications developed using the .NET Framework Pmapper as for system modeling using the Unified Modeling Language (UML) and assay methods using a black box system. Keywords: facilities city, Information Systems geografis, Unified Modeling Language (UML), pmapper.